Collective Bargaining by Civil Servants - Andras, Andy (Relations industrielles / Industrial Relations, 1958)
SummaryIn this article, the Author describes organization as a fundamental fact of life and the right of association as a civil liberty and a basic need for civil servants. Should these remain suppliant, or become truly demanding? Collective bargaining brings about important changes in the relationship between the parties which are all to the good. The Author examines various alternatives (strike, arbitration, conciliation, fact-finding boards) for dispute settlement, describes the scope of bargaining and the problems of representation of the civil servants, paving the way toward "a sounder relationship" between them and the government.